Seaweed Heat Pump Dryer with Latent Heat and Cooling Energy Recovery - Cheng Jiahao; Cao Xiang; Ge Meicai; Zhang Chunlu (Zhileng xuebao)
Conventional air convective driers for drying seaweed consume large amounts of energy as it uses fossil fuels, biomass, or electricity. Enclosed systems assisted by vapor compression heat pumps are much more energy-efficient and are widely applied to many drying processes. However, the existing simple heat pump dryer is not suitable for seaweed drying because of the significant air flow rate required. In this study, a novel seaweed heat pump dryer is proposed to recover latent heat through air bypass and cooling energy using a subcooler. The system is optimally designed with the aid of a simulation and working domain evaluation. A prototype was built for the model validation and performance analysis. The results show that the proposed system can achieve a specific moisture extraction rate (SMER) of 2.61 kg/kWh under typical seaweed drying conditions (return air temperature of 46 ℃ and relative humidity of 40%). The SMER peaks at a bypass air ratio of 0.77, and subcooling of 25 ℃, and is maintained above 1.88 kg/kWh when the return air fluctuates within a certain temperature range (46±3)℃ and relative humidity range (40%±10%).